Vestibular Function and Quality of Life in Vestibular Schwannoma: Does Size Matter? - Wagner, Judith; Glaser, Miriam; Wowra, Berndt; Muacevic, Alexander; Goldbrunner, Roland; Cnyrim, Christian; Tonn, Jörg-Christian; Strupp, Michael (Frontiers in Neurology, 2011)
Objectives. Patients with vestibular schwannoma (VS) frequently suffer from disabling vestibular symptoms. This prospective follow-up study evaluates vestibular and auditory function and impairment of quality of life due to vertigo, dizziness and imbalance in patients with unilateral vestibular schwannoma of different sizes before/ after microsurgical or radiosurgical treatment. Methods. 38 patients with unilateral vestibular schwannoma were included. 22 received microsurgery, 16 cyberknife radiosurgery. Two follow-ups took place after a median of 50 and 186.5 days. Patients received a standardized neuro-ophthalmological examination, electronystagmography with bithermal caloric testing, and pure-tone audiometry. Quality of life was evaluated with the Dizziness Handicap Inventory (DHI). Patient data was grouped and analyzed according to the size of the VS (group 1: < 20mm vs group 2: ≥ 20mm). Results. In group 1, the median loss of vestibular function was +10.5% as calculated by Jongkees Formula (range –43;+52; group 2: median + 36%, range –56; +90). The median change of DHI scores was –9 in group 1 (range –68;30) and +2 in group 2 (–54;+20). Median loss of hearing was 4dB (-42;93) in group 1 and 12dB in group 2 (5;42). Conclusions. Loss of vestibular function in vestibular schwannoma clearly correlates with tumor size. However, loss of vestibular function was not strictly associated with a long-term deterioration of quality of life. This may be due to central compensation of vestibular deficits in long-standing large tumors. Loss of hearing before treatment was significantly influenced by the age of the patient but not by tumor size. At follow-up 1 and 2, hearing was significantly worse in those patients with a large VS and after microsurgical treatment.